The Self and Shadow of Lady Diana in Spencer - Septian Dwi Putri; Maria Maria; Dina Juniar Anggraini (International Journal Multidisciplinary Science, 2026)
This research examines the portrayal of the Self and Shadow personality in the character of Lady Diana in the movie Spencer using Carl Jung’s psychoanalytic theory. The film depicts Lady Diana’s psychological struggle during Christmas 1991, a crucial moment when she considers divorcing Prince Charles and leaving the British royal family. This study applies Jung’s concept of the Collective Unconscious, focusing on the Self and Shadow archetypes, to analyze her inner conflicts. The data consist of Lady Diana’s expressions, actions, and dialogues that reflect elements of the Self and Shadow. Using a descriptive qualitative method, the findings reveal that Lady Diana is strongly influenced by her Shadow personality, manifested through emotional suppression, fear, anxiety, and resistance to royal constraints. Meanwhile, the Self emerges through her growing self-awareness and desire for personal freedom. The interaction between the Shadow and the Self significantly shapes Lady Diana’s psychological development in the film.